IMPACT OF SERVICE QUALITY, TRUST, AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY IN PT MEGA MANUNGGAL PROPERTY TBK - Stefanie, Maria Anna; Sitepu, Badikenita (Emerging Markets : Business and Management Studies Journal, 2018)
In order to compete, survive, and grow the company is required to provide a good quality services to meet the needs and desires of its customers. Companies must be able to maintain a good reputation in the eyes of its customers. A good quality services will tend to give more satisfaction to the customers who use the services of the company. With emphasis on good service it will build a long-term profitable relationships with customers while also achieving customer loyalty. Therefore, this study is aiming to determine the importance of the impact of service quality, trust and customer satisfaction at PT Mega Manunggal Tbk Property in an effort to improve customer loyalty which will affect the company's survival. A questionnaire distribution method chosen in this study is to collect primary data. Completed questionnaires designed and distributed or disseminated to all customers. SPSS for windows has been used to process the primary data.Thefindings showed that there is a significant relationship between service quality and customer loyalty, meaning that if the quality of service increases, customer loyalty will also increase.There is a significant influence between customer trust and customerloyalty,meaning that if the customer trust increases, customer loyalty will also increase.